Take a picture! The role of visual methods in understanding psychiatric patient’s everyday life - Moretti, Veronica; Brunetti, Chiara; Candaten, Andrea; Cannavò, Daniela; Manfredi, Martina; Maserati, Martina; Piccinini, Amedea; Rinaldi, Melissa; Artioli, Giovanna; Sarli, Leopoldo; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Understanding the patient's experience of mental illness can foster better support for this population and greater partnership with healthcare professionals. This study aims to explore the application of visual methods in the psychiatric field and, in particular, the experience of people suffering from psychotic disorders because it is still an open question that has not been only partially empirically examined.Methods: This qualitative study was conducted using two visual methods (auto-photography and photo-elicitation) associated with the narrative that emerged from an unstructured interview, in a clinical setting of adult Mental Health in Italy, between October 2019 and February 2020. A total of 5 patients and 5 corresponding referring healthcare professionals were identified and enrolled.  Patients were asked to produce photographs following 4 thematic areas: “Fun”, “Time”, “Something indispensable”, “Place where I feel good”.Results: A total of 85 photographs were produced. Visual methods have proved to be a useful technique in qualitative research in the area of adult psychiatry. From the interviews, it emerged that visual methods have allowed psychotic patients to use a new language to be able to communicate their emotions.Conclusions: The healthcare professionals involved also confirm the potential of this tool which, when combined with the traditional interview, is able to deepen the patient's knowledge by overcoming the verbal barriers that often make it difficult to reconstruct the individual experience of illness.